Analisis fasilitas wisata Halal di Korea Selatan : Studi kasus Seoul Central Mosque - Luthfiyyah, Salsa Faiz (Nur Science Institute, 2022)
South Korea, as a mecca country in various sectors, easily steals the international community's attention. These conditions make South Korea try to continue improving tourism quality. Considering the Islamic population is almost sixty percent of the world's population, South Korea started introducing halal industry in 2015. The increasing number of Muslim tourists to South Korea but the provision of inadequate facilities are one point of the weakness of South Korean halal tourism. The government is trying to overcome these weaknesses by providing halal facilities, starting with places of prayer. This article analyzes the availability of halal facilities in South Korea that have implemented the halal tourism industry. This article uses qualitative methods with data collection techniques through literature study techniques. The results are that places of prayer continue to increase and can support the success of halal tourism and provide benefits, although many challenges must be overcome.